Disguised Employment Relationship Towards Platform-Based Drivers: Indonesian and United Kingdom Law Perspective - Lia Christine; Achmad Benyamin Daniel; Tresnawati Tresnawati; Catharina Dewi Wulansari (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Digital technology has created non-conventional employment through platform applications, exemplified by platform-based drivers in Indonesia. Their relationship with App Provider Companies is governed by partnership agreements, resulting in unclear legal status and limited labour protection. This study examines the legal vacuum that leaves drivers without social security and workers’ rights, despite fulfilling employment elements; work, wages, and control. Using a juridical normative approach, it finds that partnership agreements may disguise employment to evade employer obligations. The UK Uber case supports recognising drivers as workers entitled to protection. Special regulations are needed to formalise their status and safeguard rights and welfare in the digital economy.